2010
DOI: 10.1371/journal.pone.0013815
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Reduce the Parasite Burden in Leishmania (Leishmania) amazonensis-Infected Macrophages

Abstract: BackgroundStudies on the role of neutrophils in Leishmania infection were mainly performed with L. (L) major, whereas less information is available for L. (L) amazonensis. Previous results from our laboratory showed a large infiltrate of neutrophils in the site of infection in a mouse strain resistant to L. (L.) amazonensis (C3H/HePas). In contrast, the susceptible strain (BALB/c) displayed a predominance of macrophages harboring a high number of amastigotes and very few neutrophils. These findings led us to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 37 publications
(38 reference statements)
3
27
1
1
Order By: Relevance
“…A similar result was obtained in a mouse model of visceral infection, which showed that the depletion of neutrophils led to a rapid increase in the early splenic parasite burden but had no effect on the chronic disease [45]. Our failure to observe early parasite control contrasts with studies that demonstrated Leishmania killing capacity of neutrophils [13, 15, 23], as early as 3 hours post-infection [14] However, it agrees with observations indicating that L . donovani is able to safely survive in the phagosomal compartment during 24-48h [16].…”
Section: Discussionsupporting
confidence: 89%
“…A similar result was obtained in a mouse model of visceral infection, which showed that the depletion of neutrophils led to a rapid increase in the early splenic parasite burden but had no effect on the chronic disease [45]. Our failure to observe early parasite control contrasts with studies that demonstrated Leishmania killing capacity of neutrophils [13, 15, 23], as early as 3 hours post-infection [14] However, it agrees with observations indicating that L . donovani is able to safely survive in the phagosomal compartment during 24-48h [16].…”
Section: Discussionsupporting
confidence: 89%
“…The same effect was observed in the control of L. amazonensis , where it was shown that TNF-α, elastase and platelet activation factor, produced by neutrophils, were responsible for parasite killing. On the other hand, this study also showed that NO and ROIs were not involved in the clearance of the parasite, as has been observed with other Leishmania species [46]; we consider that, in both cases, it is also possible that neutrophils secrete MRPs, and this secretion helps to control the infection. Contrary to what was shown by Ribeiro et at.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have assessed the ability of neutrophils to reduce Leishmania burden in infected macrophages [1820]; however, the effect of neutrophils on L. braziliensis amastigote-infected macrophages remains uncharacterized. To explore the interaction between neutrophils and infected macrophages, we loaded bone marrow-derived macrophages with amastigotes and added thioglycollate-induced (control) neutrophils for 24 h. At the end of incubation, we added parasite medium to liberate surviving parasites from macrophages and assessed subsequent parasite growth after 3–4 days.…”
Section: Resultsmentioning
confidence: 99%